2020
DOI: 10.3390/plants9121729
|View full text |Cite
|
Sign up to set email alerts
|

The Geomagnetic Field (GMF) Modulates Nutrient Status and Lipid Metabolism during Arabidopsis thaliana Plant Development

Abstract: The Geomagnetic field (GMF) is a typical component of our planet. Plant perception of the GMF implies that any magnetic field (MF) variation would induce possible metabolic changes. In this work was we assessed the role of the GMF on Arabidopsis thaliana Col0 mineral nutrition and lipid metabolism during plant development. We reduced the local GMF (about 40 μT) to Near Null Magnetic Field (NNMF, about 30 nT) to evaluate the effects of GMF on Arabidopsis in a time-course (from rosette to seed-set) experiment by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…At the root level, two-way ANOVA revealed that (i) NA significantly affected Fe ( p < 0.001), Zn ( p < 0.001), and Mo ( p < 0.001) content; (ii) MF significantly affected Cu ( p < 0.001) and Zn ( p < 0.05); (iii) the NAxMF interaction significantly affected only Cu content ( Table 1 ). In particular, under control conditions, NNMF-exposed plants displayed low Fe content compared to GMF- exposed plants, while the content of other metals did not change, in agreement with our previous findings [ 14 ]. Under –Fe, the content of Fe, Mn, Cu, and Zn in the roots were higher in the NNMF- than in the GMF-exposed plants ( p < 0.05; Table 1 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…At the root level, two-way ANOVA revealed that (i) NA significantly affected Fe ( p < 0.001), Zn ( p < 0.001), and Mo ( p < 0.001) content; (ii) MF significantly affected Cu ( p < 0.001) and Zn ( p < 0.05); (iii) the NAxMF interaction significantly affected only Cu content ( Table 1 ). In particular, under control conditions, NNMF-exposed plants displayed low Fe content compared to GMF- exposed plants, while the content of other metals did not change, in agreement with our previous findings [ 14 ]. Under –Fe, the content of Fe, Mn, Cu, and Zn in the roots were higher in the NNMF- than in the GMF-exposed plants ( p < 0.05; Table 1 ).…”
Section: Resultssupporting
confidence: 92%
“…Since we previously identified a link between Fe and Cu under NNMF conditions [ 14 ], we monitored the expression of SPL7 and miR408 , two master regulator genes involved in the cross-link between Fe and Cu homeostasis in plants [ 16 , 17 ]. Two-way ANOVA revealed that NA ( p < 0.001), MF ( p < 0.001), and NAxMF ( p < 0.05) affected SPL7 expression ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the natural components of our planet, such as water, temperature, climate and electric charges, Earth's magnetic field or geomagnetic field (GMF) is a component that influences many biological processes in plants [15][16][17][18]. As a sessile organism, plants show different levels of morphophysiological and molecular responses under different magnetic field (MF) intensities, such as shoot, root and stem elongation, photosynthetic performance, plant nutrient uptake and the expression of several genes associated with photoreceptors [8,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the biomass accumulation of Arabidopsis was 36% lower when the plants grew to the reproductive stage, and the number of siliques and the production of seeds per plant was also lower, resulting in an approximately 20% decrease in the harvest index [Xu et al, 2013]. The leaf area index was also reduced during the flowering and seed set stages under HMF conditions, accompanied by a reduction in fresh and dry mass [Islam et al, 2020b].…”
Section: The Biological Effects Of Hmfmentioning
confidence: 99%